Mites associated with maize in Mexico - Chaires-Grijalva, Martha Patricia; Serrano-Domínguez, Ana Karen; Coronado-Blanco, Juana María (Revista Mexicana de Ciencias Agrícolas, 2021)
For Mexico, maize (Zea mays L.) is one of the crops with the greatest cultural and economic importance. One of the problems that decrease its production is the presence of primary pests, which when controlled with chemical insecticides contribute to the appearance of others considered secondary, such as mites. In the cultivation of maize, nine species of mites belonging to the families Acaridae and Tetranychidae and one unidentified species of Iolinidae have been recorded. The species with a wide distribution record belong to the genera Oligonychus and Tetranychus, belonging to the family Tetranychidae, mainly of phytophagous habits. In infested plants, a whitish or tanned appearance of the foliage is observed. Economically important populations appear during June, July and August, particularly if the weather is hot and dry. The greatest impact on yield occurs when mites damage the leaves at or above the level of the cob. The stages of the crop where more damage is quantified are at the beginning of flowering and grain filling, since the presence of high populations of mites in these stages causes stunted cobs with small grains to occur due to the dehydration they cause. Cultural practices, crop improvement, natural enemies and acaricides can be used as management strategies. Therefore, this review of species of mites that are considered as a pest in one of the most important crops in Mexico aims to present different biological and ecological aspects important in the mite-maize interaction.
Keywords: Acaridae; economic importance; foliage; Iolinidae; Tetranychidae